Market efficiency and asymmetric relationship between South Asian stock markets: An empirical analysis - Syed Jawad Hussain Shahzad; Muhammad Zakaria; Sajid Ali; Naveed Raza (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
This paper examines market efficiency and asymmetric cointegration among the South Asian stock markets using monthly data from January 1998 to December 2013. The structural breaks and wavelet based unit root tests indicate that the markets are efficient at least in the weak form. We use asymmetric cointegration and asymmetric error correction models to examine the dynamic relationship between the selected stock markets. Results suggest that Indian stock market impacts Pakistani stock market in long run. Bangladesh stock market impacts Sri Lankan stock market and the speed of adjustment to the positive shocks is higher and thus stock prices adjust quickly to the good news in comparison to the bad ones. The asymmetric error correction model shows unidirectional causality running from Indian stock market (Sri Lankan stock market) to Pakistani stock market (Bangladeshi stock market). The analysis provides implications for the investors while assigning the optimal weight of assets during portfolio formulation.
Keywords: 330; asymmetric co-integration; market efficiency; stock markets; south Asia